Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Infinite series convergence/divergence and finding the sum?
sum from n=1 to infinity of 4/((n^2)+4n+3)
If this series converges, find its sum, if it diverges, explain why.
5 Answers
- BrendaLv 79 years agoFavorite Answer
4/n²+4n+3
4/(n+1)(n+3)
4Σ(with n from 1 to ∞) 1/(n+1)(n+3)
this is a telescoping series:
1/(n+1)(n+3) =A/(n+1) +B/(n+3)
1=A(n+3)+B(n+1)
n=-3:
1=B(-2)
-2B=1 =>B=-1/2
n=-1:
1=2A =>A=1/2
4Σ 1/2(n+1) -1/2(n+3)
2Σ 1/n+1 -1/n+3
n=1,2,3,4,etc
[1/2-1/4]+[1/3-1/5]+[1/4-1/6]+[1/5-1/8]+[-1/k+2]+[-1/k+4]
except from 1/2 and 1/3 the rest of the terms will cancel.
1/2 +1/3 -1/k+2 -1/k+4
as n→ ∞
lim [ 1/2+1/3 -1/k+2-1/k+4] = 5/6
originally we had 2Σ 1/n+1 -1/n+3
the series converges to 2(5/6) = 10/6
- θ βяιαη θLv 79 years ago
For n ≥ 1, n^2 + 4n + 3 > n^2 > 0, so we have:
0 < 1/(n^2 + 4n + 3) < 1/n^2 ==> 0 < 4/(n^2 + 4n + 3) < 4/n^2.
Since ∑ 4/n^2 (from n=1 to infinity) converges because it is a multiple of a convergent p-series, the series in question converges by the Comparison Test.
Now, to find the sum of this series, notice that n^2 + 4n + 3 can be nicely factored to (n + 3)(n + 1), so we can find the sum by using partial fractions. For some A and B, we have:
4/[(n + 3)(n + 1)] = A/(n + 3) + B/(n + 1).
Multiplying both sides by (n + 3)(n + 1) to clear the fractions gives:
4 = A(n + 1) + B(n + 3) = (A + B)n + (A + 3B).
Comparing the coefficients of n (note that the coefficient of n on the left side is 0) gives:
A + B = 0 ==> A = -B.
Then, comparing the constants gives:
A + 3B = 4,
but since A = -B, this becomes:
-B + 3B = 4 ==> B = 2.
Using this value of B and the fact that A = -B, A = -2. So, the required partial fraction decomposition is:
4/[(n + 3)(n + 1)] = 2/(n + 1) - 2/(n + 3).
Now, let us consider the sum of the first k terms of the series. Using the above decomposition:
∑ 4/(n^2 + 4n + 3) (from n=1 to k) = 2 ∑ [1/(n + 1) - 1/(n + 3)] (from n=1 to k)
= 2{[1/2 + 1/3 + 1/4 + ... + 1/(k + 1)] - [1/4 + 1/5 + 1/6 + ... + 1/(k + 3)]}
= 2[1/2 + 1/3 - 1/(k + 1) - 1/(k + 2)], as all other terms cancel in pairs.
Letting k --> infinity yields the required sum to be 2(1/2 + 1/3 - 0 - 0) = 5/3.
I hope this helps!
- nleLv 79 years ago
Compare with 4/n^2
Since 4/n^2 converges ( p-series) then 4/((n^2)+4n+3)
converges.
To find the sum use
4/((n^2)+4n+3) = 2 /(n+1) - 2/(n+3)
- 9 years ago
the series converges let's prove it
n^2 +4n +3
=n^2+4n +4 -1
=(n+2)^2-1
=(n+1)(n+3)
so the nth term is
4/[(n+1)(n+3)]
taking a partial fraction expansion you get
2/(n+1) - 2/(n+3)
this is now a telescoping series and the only terms which are not canceled are 2/2+2/3
(convince yourself: 2/2-2/4+2/3-2/5+2/4-2/6+2/5-2/7.........)
and therefore the sum is equal to 2/2+2/3 = 5/6
hope this helps
- How do you think about the answers? You can sign in to vote the answer.
- ?Lv 45 years ago
considering the fact that I spent the time working in this subject... This series converges by way of the Alternating series try. (i) {(sqrt(n))sin(a million/n)} is reducing for sufficiently super n. that is maximum only considered by way of Calculus. permit f(x) = x^(a million/2) sin(a million/x). ==> f'(x) = (x^(-3/2)/2) [x sin(a million/x) - 2 cos(a million/x)]. As x-->infinity, x sin(a million/x) - 2 cos(a million/x) = sin(a million/x) / (a million/x) - 2 cos(a million/x) --> a million - 2 = -a million. So, f'(x) < 0 for sufficiently super n. for this reason f is reducing for sufficiently super n. (ii) lim(n-->infinity) n^(a million/2) sin(a million/n) = lim(n-->infinity) n^(-a million/2) * [sin(a million/n) / (a million/n)] = 0 * a million = 0. ------------------------------------ i desire this helps! fact: i'm no longer too specific if this sum has a closed form. regardless of if, considering the fact that this series is alternating, possible approximate it with the 1st n words with an blunders in magnitude no bigger than the (n+a million)-th term.